Heart of a stranger : an unlikely rabbi's story of faith, identity, and belonging - Buchdahl, Angela, 1972- (Pamela Dorman Books/Viking, 2025)
"From the first Asian American to be ordained as a rabbi, a stirring account of one woman's journey from feeling like an outsider to becoming one of the most admired religious leaders in the world Angela Buchdahl was born in Korea and grew up in Tacoma, Washington, the daughter of a Korean Buddhist mother and Jewish American father. Profoundly spiritual from a young age, felt a connection to God when only a child and felt the first stirrings to become a rabbi at age sixteen. Despite the naysayers and periods of self-doubt-would a mixed-race woman ever be seen as authentically Jewish and entitled to lead a congregation-she stayed the course, which took her first to Yale, then to rabbinical school, cantorial school, and finally to the pulpit of one of the largest, most influential congregations in the world. Today, Angela Buchdahl is revered by Jews and non-Jews alike for her invigorating, joyful approach to worship, and her belief in the power of faith, gratitude, and responsibility for each other, regardless of religion. She does not shy away from challenging topics, be it racism within the Jewish community to sexism she confronted when she aspired to the top job. Buchdahl has also been a sought-after leader and voice through some of the most challenging moments in recent history, from the murder of George Floyd to the hostage standoff in Colleyville, Texas to the horrors of October 7th. Buchdahl's consistent message is that it is up to us to strive for a world of more humanity, especially in today's challenging times. Angela Buchdahl has gone from outsider to officiant, from feeling estranged to feeling embraced-and she's emerged with a deep feeling of being bound to a larger whole and mission. Here, she has written a book that is both a memoir and a spiritual guide for everyday living, which is exactly what so many of us crave right now"-- Provided by publisher.